Is population beneficial to economic growth? An empirical study of China - Furuoka, Fumitaka (Springer Verlag, 2018)
This study examined the relationship between population growth and economic growth in China. It employed innovative econometric methods including the breakpoint unit root test, the autoregressive distributed lag method, the bounds test for cointegration and the Toda–Yamamoto causality test. The empirical analysis detected a negative long-run relationship and bidirectional causality between population and economic growth. This means that the findings suggested that population growth was a cause and an effect of economic growth. The study concluded that population expansion could be detrimental to economic growth in China. At the same time, economic growth could stem population expansion.